2022
DOI: 10.1136/bmjno-2022-000309
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome following SARS-CoV-2 vaccination in the UK: a prospective surveillance study

Abstract: ObjectiveTo investigate features of Guillain-Barré syndrome (GBS) following SARS-CoV-2 vaccines and evaluate for a causal link between the two.MethodsWe captured cases of GBS after SARS-CoV-2 vaccination through a national, open-access, online surveillance system. For each case, the certainty of GBS was graded using the Brighton criteria, and the relationship to the vaccine was examined using modified WHO Causality Assessment criteria. We compared age distribution of cases with that of prepandemic GBS cases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…The second point raised, regarding the number of cases we observed specifically after the AstraZeneca vaccine, appears, as mentioned by Galassi et al, in keeping with Keh et al's subsequent report, which also demonstrated an increased risk with this vaccine. 3 Similarly, Patone et al 4 and, more recently, Tamborska et al, reporting for the UK Covid vaccine GBS Study Group, 5 both described an excess risk with the AstraZeneca vaccine in UK-wide studies, in keeping with our regional findings. Keh et al reported an increased risk comparable with that of the 1976 swineflu vaccine, 3 which itself is a notable finding that should be made known to the medical community and patients.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…The second point raised, regarding the number of cases we observed specifically after the AstraZeneca vaccine, appears, as mentioned by Galassi et al, in keeping with Keh et al's subsequent report, which also demonstrated an increased risk with this vaccine. 3 Similarly, Patone et al 4 and, more recently, Tamborska et al, reporting for the UK Covid vaccine GBS Study Group, 5 both described an excess risk with the AstraZeneca vaccine in UK-wide studies, in keeping with our regional findings. Keh et al reported an increased risk comparable with that of the 1976 swineflu vaccine, 3 which itself is a notable finding that should be made known to the medical community and patients.…”
supporting
confidence: 86%
“…cohorts from Europe and America. 5 We disagree with Galassi et al about the statistical methods that we used, as also used in other studies, 3,5 which compared proportions of subjects with specific features between two groups, and which we consider both adequate and appropriate.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Regarding other types of COVID-19 vaccines, seven cases of GBS were reported following BNT162b2 mRNA vaccine among approximately 4 million recipients, and a recent report issued by the UK Health Security Agency concluded that the risk of developing GBS after ChAdOx1vaccine adds 5.6 extra cases of GBS per million doses. 10 , 11 Hence, for detailed description and comparison of the clinical and prognosis information regarding the association between COVID-19 vaccines and MFS, we systematically searched in “PubMed,” “Web of Science,” and “Cochrane” using the keywords“COVID-19” or “SARS-CoV-2,” “vaccination” or “vaccine,” “Miller Fisher syndrome” or “MFS” or “acute ataxic neuropathy” or “acute ophthalmoparesis” from 1 January 2020 to 30 July 2022. The flow diagram of publication identification is listed in Figure 1 .…”
Section: Discussionmentioning
confidence: 99%